Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1084/jem.184.3.1101
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficacious lymphocyte chemoattractant, stromal cell-derived factor 1 (SDF-1)

Abstract: SummaryChemotactic factors are postulated to direct emigration of lymphocytes from the blood stream into sites of inflammation. Members of a family ofchemotactic cytokines, termed chemokines, have been shown to attract lymphocytes but efficacy, i.e., the maximal percentage of attracted cells, has been low. We have identified a highly efficacious lymphocyte chemotactic activity in the supernatants of the murine bone marrow stroma cell line MS-5 which attracts 10-fold more lymphocytes in vitro than currently des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,009
3
8

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,361 publications
(1,059 citation statements)
references
References 27 publications
35
1,009
3
8
Order By: Relevance
“…At high power (i), some of the epithelioid macrophages can be seen to contain acidfast bacilli (arrows). 374,213,156,19,181,415,493,218,196,265,396,425,D11Mit226,19,20,349,194,39,67,224,103 109,145,206,541,150,361,221,209 D12Mit12,153,34,14,118,233,20 D2Mit1,32,367,61,91,436,164,401,225,311,200 D13Mit271,60,139,250,145,293,35 D3Mit176,306,69,241,51,72,156,106,17,128 D14Mit207, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high power (i), some of the epithelioid macrophages can be seen to contain acidfast bacilli (arrows). 374,213,156,19,181,415,493,218,196,265,396,425,D11Mit226,19,20,349,194,39,67,224,103 109,145,206,541,150,361,221,209 D12Mit12,153,34,14,118,233,20 D2Mit1,32,367,61,91,436,164,401,225,311,200 D13Mit271,60,139,250,145,293,35 D3Mit176,306,69,241,51,72,156,106,17,128 D14Mit207, …”
Section: Resultsmentioning
confidence: 99%
“…The chemokine receptor CXCR4 (map position 67 cM) is expressed on T lymphocytes and binds to the SDF-1␣/␤ ligand, and plays an important role in the activation of naïve CD45RA + T cells. 32 It has been proposed that antigen-presenting, SDF-1 secreting dendritic cells can acti- vate naïve CXCR4-positive naïve T cells upon migration to lymph nodes. 33 This region also contains the gene for interleukin 10 (IL-10; map position 70 cM), a cytokine produced by T cells (Th2) and macrophages, that blocks IFN-␥ synthesis by T cells, and cytokine synthesis by macrophages.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…While some authors were unable to detect expression of CXCR4 [6,7], others have described binding of SDF-1 § , SDF-1 § -induced Ca 2+ flux and migration [8][9][10]. We have detected a clear expression of CXCR4 on neutrophils from the synovial fluid of patients with different inflammatory joint diseases, whereas CXCR4 was hardly detectable in the peripheral blood of patients or normal blood donors, suggesting that CXCR4 on neutrophils could be functionally relevant in the setting of inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…30 SDF-1 is a chemokine that plays an important role in B-cell development, trafficking, and activation. [8][9][10][11] Several studies suggested that SDF-1 may have a crucial role in the development of autoimmune disease. Matin et al 31 demonstrated that the chemokine SDF-1 may be an essential chemoattractant in trafficking and migration of mature autoreactive B cells from bone marrow to the periphery or inflammatory sites in the development of autoimmune diabetes.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…8 It is a chemoattractant for monocytes, naive and memory T lymphocytes, and B lymphocytes. [9][10][11] SDF-1 is also a costimulatory factor for CD4 þ T-lymphocyte activation. 12 In view of the presence of an important mononuclear cell infiltrate in SO, MCP-1 and SDF-1 are candidate chemokines for investigation.…”
Section: Introductionmentioning
confidence: 99%